Situation Report: Czechoslovakia, 27 December 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Mitterrand's Visit / by Peter Martin Changes in the CPCS Leadership / by Jiri Pehe; Jan Obrman Vasil Bilak Goes / by Vladimir Kusin Vail Bilak: A Short Biographical Note / by Jan Obrman; Jiri Pehe; Vladimir Kusin Middle East Conference in Prague / by Jan Obrman Church-State Relations / by Peter Martin Is the Regime Becoming More Tolerant? / by Jiri Pehe The Leadership's New Tactics toward Independent Groups / by Jiri Pehe Alexander Dubcek in the Limelight / by Jiri Pehe Pre-Christmas Shortage of Consumer Goods / by Jan Obrman